2008
DOI: 10.1056/nejmsa071456
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Intervention to Improve Obstetrical Care

Abstract: A multifaceted behavioral intervention increased the prophylactic use of oxytocin during the third stage of labor and reduced the use of episiotomy. (ClinicalTrials.gov number, NCT00070720 [ClinicalTrials.gov]; Current Controlled Trials number, ISRCTN82417627 [controlled-trials.com].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
156
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(167 citation statements)
references
References 22 publications
(1 reference statement)
7
156
0
4
Order By: Relevance
“…Out of 8,104 de-duplicated titles and abstracts, nine studies were deemed relevant in our review. [16][17][18][19][20][21][22][23][24] Review of full text articles led to exclusion of three studies because the intervention was not relevant [22][23][24] and one study because it was a feasibility study. 21 Five relevant randomized controlled trials met the full inclusion criteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 8,104 de-duplicated titles and abstracts, nine studies were deemed relevant in our review. [16][17][18][19][20][21][22][23][24] Review of full text articles led to exclusion of three studies because the intervention was not relevant [22][23][24] and one study because it was a feasibility study. 21 Five relevant randomized controlled trials met the full inclusion criteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18][19][20] Five cluster randomized controlled trials (RCT) examining educational interventions for seeking, appraising, and applying evidence from systematic reviews in decision-making by clinicians were identified (Tables 1). [16][17][18][19][20] A meta-analysis of study outcomes was not possible due to the heterogeneity in the format of the interventions, the settings, and clinical areas being addressed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations